Análise da síntese de IL-12 em linfócitos T CD4+ e correlação com fatores de transcrição em pacientes com câncer avançado - VIEIRA, Jéssica Ferreira (2017)
In the tumor context, the immune system plays roles that can prevent development or progression of tumor. Thus, the production of cytokines by CD4+ T lymphocytes represents a crucial phenomenon in the immune response, because the variations in this regulation may result in an inadequate response. Previously, our research group demonstrated that CD4+ T lymphocytes from advanced cancer patients expressed interleukin-12 and the same was applied to mice induced breast cancer with DMBA (7,12-Dimethylbenzanthracene). The aim of the present study was to evaluate the synthesis of IL-12 in CD4+ T lymphocytes from the peripheral blood of cancer patients, correlating with the expression of T-bet, GATA-3, RORγt and FoxP3 transcription factors. The CD3+CD4+IL-12+ T cells were isolated from the peripheral blood obtained from cancer patients, using flow cytometry technique with cell sorting principle and submitted to transcriptional profile analysis. The results demonstrate a significantly higher percentage of CD3+CD4+IL-12+ T lymphocytes in the peripheral blood of cancer patients (p <0.0001). In addition, these express the transcription factor RORγt, and some may coexpress the T-bet factor. It has been observed that some serum factor (s) present in the serum of cancer patients are still capable of inducing the differentiation of CD3+CD4+IL-12+ T lymphocytes, being remarkable the increase in the percentage of these cells in stimulated cultures with serum (p = 0.0020). However new investigations are needed to understand this lymphocyte phenotype.